Analisis Faktor-Faktor yang Mempengaruhi Persepsi Atas Informasi Akuntansi Keuangan Serta Keberhasilan dalam Mengelola Perusahan Kecil dan Menengah (Studi Empiris Pada UMKM Industri Makanan di Wonosobo) - Imam Ariono; Bambang Sugiyanto (Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an (UNSIQ) Wonosobo, 2018)
In order to overcome the problem of economic inequality and social inequality, a strategic step is grow and develop small businesses that have the characteristics of, among others, technology is simple, and is able to absorb the labor force so as to realize equal opportunity to strive and income distribution. In addition, small businesses are sub sectors of economic activity plays an important role in strengthening macroeconomic structure. In the Indonesian economy, the role and contribution of entrepreneurs on the scale of small and medium enterprises is very large, not only in terms of employment which exceeds 90%, but its contribution to GDP Indonesia more than 50%, (Ministry of Cooperatives and SMEs 2014). This study aims to prove the influence of attitude, personality, motivation, experience the perception of entrepreneurs on financial and accounting information to prove the influence of employers' perception on the use of financial accounting information to business success. Research was conducted on SME food industry in Wonosobo regency. Sampling of the population using purposive sampling method The samples in this study using purposive sampling technique is a technique take samples with specific criteria. The number of samples in this study were 45 SME food. The analysis tool used is multiple linear regression. The results of this study indicate that the attitude positive effect on the perception of entrepreneurs on the use of financial accounting information. Personality positive effect on the perception of entrepreneurs on the use of financial accounting information. Motivation positive effect on the perception of entrepreneurs on the use of financial accounting information. Experience positively affects the perception of entrepreneurs on the use of financial accounting information. Perception of entrepreneurs on the use of financial accounting information positive effect on business success. Keywords : Attitude, personality, motivation, experience, education, perception of financial accounting information, business success